Evolução dos sintomas residuais e sua relação com comorbidades em pacientes com síndrome pós-covid-19 - RODRIGUES, Emily Saboia Moura (2024)
Introduction: Survivors of the COVID-19 pandemic must deal with disabling symptoms that affect the most diverse organ systems and that persist for more than 3 months after the acute phase of the infection. These manifestations were called post-COVID syndrome by the World Health Organization. Objective: This study aimed to evaluate the influence of metabolic comorbidities on the intensity of persistent symptoms reported by patients and the evolution of these complaints over time. Methods: This is an analytical longitudinal study, with 100 individuals who presented persistent residual symptoms after at least 3 months of the acute phase of COVID from april 2022 to april 2023. The intensity of symptoms was assessed in 2 medical appointments, with an interval of at least 6 months and a maximum of 12 months, in which previous comorbidities, anthropometric parameters and laboratory tests were also investigated. Results: 76% of participants were women and the overall average age was 54.3 years. The majority of patients had a mild acute infection (53%), did not experience reinfection (65%), had already received 3 doses of vaccine in the first consultation (51%). The most prevalent symptoms were neuropsychiatric, musculoskeletal and hair loss. The most prevalent metabolic comorbidities were hypertension, obesity and dyslipidemia. There was significant improvement (p<0.001) for all 28 symptoms evaluated, using the Wilcoxon test. There was a considerable increase in pre-diabetes and dyslipidemics after COVID infection. There was no association between the outcome of residual symptoms and metabolic comorbidities, using the Chi-Square and Fisher's Exact tests (p > 0.05). There was no association between the variables reinfection, vaccination and time after acute infection with the evolution of residual symptoms. Conclusion: The intensity of residual symptoms decreased over 12 months. There has been a significant increase in the prevalence of prediabetes and dyslipidemia following COVID infection. Metabolic comorbidities, in isolation, did not influence the outcome of each symptom.